The Impacts of FDI Inflows of China on Intra Industry Trade of Indonesiaâs Manufacturing Industry - Verena, Vidita Vergia (RIEBS, 2016)
This article is to examine the impact of Chinese firmsâ FDI to Indonesia on the development of intra-industry trade between two countries, measured by Grubel-Lloyd index. Using Pooled Least Square (PLS) regression method, this article shows that the increase of Chinese firmsâ investment in Indonesiaâs industry, particularly in manufacturing industry, demonstrated strongly positive effect in the intensification of intra-industry trade. Additionally, this article also finds that the other components such as factor endowments as well as trade openness between two countries and the existence of trade integration are also important determinants of the development of intra-industry trade between two countries.